PENGINDONESIAAN ISTILAH MIKROMORFOLOGI TANAH YANG DIGUNAKAN DALAM "HANDBOOK FOR SOIL THIN SECTION DESCRIPTION [Bullock et al., 1985]" - Widiatmaka Widiatmaka; Budi Mulyanto; Astiana Sastiono (Jurnal Ilmu Tanah dan Lingkungan, 1999)
Micromorphology is a branch of science in soil science. In micromorphological studies, soil samples are first prepared as a thin slice (with various methods), then the phenomena inside are examined using a microscope. By knowing the composition, shape, orientation, distribution patterns, structures, etc., the phenomena that occur can be interpreted, both regarding the composition of the soil, the relationship between components and the dynamics of the process that has been, moderate or expected to occur in the soil. Thus, micromorphology can and is very prospective to be developed and applied for various uses outside the field of soil science.